Unusual paediatric spinal myxopapillary ependymomas: unique molecular entities or pathological variations on a theme? - Rogers, Sasha; Jones, David T. W. (Journal of clinical neuroscience, 2018)
Ependymomas are the commonest type of spinal glioma which represent a group of relatively benign tumours. Myxopapillary ependymoma (MPE) is a common variant found within the distal spinal cord around the conus. These two entities are clearly differentiated on the basis of their characteristic histological and molecular features. Rare variants of MPE’s are described in the literature to have the propensity to metastasise and grow in extraspinal locations despite appearing histologically identical to their more benign relatives. Here, we describe two unusual cases of MPE and utilise DNA methylation analyses to compare their molecular signatures with known molecular subtypes of ependymoma in an attempt to distinguish whether these tumours represent a unique subset of disease.